1997
DOI: 10.1159/000291517
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Polyp as Risk Factor for Hysteroscopically Diagnosed Endometrial Polyps

Abstract: A case-control study was conducted searching through 590 diagnostic hysteroscopies in order to identify potential risk factors for endometrial polyps. Case (hysteroscopically positive for endometrial polyps) and control groups were compared for age, parity, cervical polyp, menopausal status, smoking and current use of contraceptive pills. A higher prevalence of endometrial polyps was found among women with a cervical polyp (26.9%) compared to those without a cervical polyp (7.1 %, Χ2 = 27.52, p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
1
11
0
2
Order By: Relevance
“…Aynı çalışmada özellikle postmenopozal olgularda endometrial polip birlikteliğinin %56.8 olması nedeniyle servikal polip olan hastalarda diagnostik histeroskopi yapılması önerilmiştir. Baş-ka bir çalışmada servikal polip saptanan olguların endometriumunun değerlendirilmesinde %26.9 oranında endometrial polip saptanmıştır (23). Çalışmamızda servikal polip nedeniyle endometrium örneklemesi yapılan olguların 11' inde endometrial polip tespit edilmiştir.…”
Section: Discussionunclassified
“…Aynı çalışmada özellikle postmenopozal olgularda endometrial polip birlikteliğinin %56.8 olması nedeniyle servikal polip olan hastalarda diagnostik histeroskopi yapılması önerilmiştir. Baş-ka bir çalışmada servikal polip saptanan olguların endometriumunun değerlendirilmesinde %26.9 oranında endometrial polip saptanmıştır (23). Çalışmamızda servikal polip nedeniyle endometrium örneklemesi yapılan olguların 11' inde endometrial polip tespit edilmiştir.…”
Section: Discussionunclassified
“…[8][9][10][11][12][13][14][15][16][17] In this study, the obesity prevalence in cervical group and control group was 32 (1%), and 23 (7%), respectively. Obese women have also a higher risk of insulin resistance, hyperinsulinemia and hyperandrogenemia.…”
Section: Discussionmentioning
confidence: 51%
“…6,7 A higher prevalence of endometrial polyps was found among women with a cervical polyp (26.9%). 9 Additionally, a relationship between cervical polyps with endometrial hyperplasia and endometrial polyps have been observed. [9][10][11][12] Therefore, cervical polyps may share the same risk factors.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In another study, this figure was 26.9% (Vilodre et al, 1997). Routine excision of the cervical polyps is recommended regardless of symptomatology and simultaneous endometrial evaluation with histopathologyc examination should be done (Coeman et al, 1993;Vilodre et al, 1997). In our clinic we routinely perform endometrial sampling in patient with cervical polyps.…”
Section: Discussionmentioning
confidence: 96%